Avaliação do ciclo de vida de estruturas de solos reforçados com geossintéticos - Araújo Júnior, Luiz Paulo Vieira de (Universidade Federal de São Carlos, 2025)
Geosynthetics are versatile materials with great potential for use in civil construction, offering advantages such as ease of use, cost-effectiveness, and environmental benefits. However, despite their many qualities, most research on geosynthetics focuses on technical feasibility analysis or experimental studies. Although the number of Life Cycle Assessment (LCA) studies in Civil Engineering is growing, there are still gaps regarding geosynthetics, particularly soils reinforced with these materials. Studies on the subject are generally limited to the manufacturing and construction stages, ignoring a complete life cycle analysis. This limited scope, by definition, ignores long-term environmental impacts, a practice that often stems from the difficulty in obtaining data on other stages and uncertainty about the final destination of the materials. This gap is exacerbated by the concentration of studies in European and North American countries, disregarding the particularities of the South American context. This approach results in a decontextualized LCA, creating a distorted view of actual environmental performance and underestimating efficient regional solutions, perpetuating a reliance on metrics that do not fully address the local context. Therefore, this research aimed to analyze, using LCA methodology and material circularity analysis, geosynthetic-reinforced soil structures and compare them with a traditional structure, considering the particularities of the South American context. The methodology included an environmental analysis through a complete LCA of the structures, evaluating the potential impacts of three structures: two geosynthetic-reinforced soil structures with geogrid and woven geotextile; and another traditional concrete gravity structure, all analyzed using the ReCiPe method. Additionally, material circularity was assessed using the Material Circularity Indicator (MCI) for the main constituents of the three structures. Finally, scenarios involving the addition of recycled materials to replace virgin materials and the planting of vegetation on the face of the structure were analyzed. The results showed that geosynthetic-reinforced soil structures had a lower environmental impact compared to concrete structures, with a reduction of at least 80% in most categories analyzed. It was also observed that the process with the greatest potential impact was the execution process, followed by the fabrication process for all three structures analyzed. The circularity analysis, in turn, indicated that, as recycled materials were added, both structures increased the MCI indicator, with gains of up to 250% for geosynthetic-reinforced soil structures and 300% for the traditional structure. Therefore, it was concluded that the LCA and circularity analysis methodologies were effective in qualitatively and quantitatively assessing the potential impacts of the structures, demonstrating that geosynthetic-reinforced soil structures can be considered environmentally more sustainable when compared to a traditional concrete structure
Life cycle assessment of geosynthetic reinforced soil structures
Keywords: Geotecnia ambiental; Mudanças climáticas; Sustentabilidade; Materiais de contenção alternativos; Circularidade dos materiais; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis